Redescription of Caridina cucphuongensis Dang, 1980 (Crustacea: Decapoda: Atyidae) from Cuc Phuong National Park, Northern Vietnam - Yen, Phan Thi; Klotz, Werner; Rintelen, Thomas von; Dong, Dang Van; Tu, Do Van (Academia Journal of Biology, 2021)
The freshwater shrimp species Caridina cucphuongensis (family Atyidae) was poorly described by Dang (1980). Moreover, the taxonomic status of this species is hard to verify as the types have been lost. This study provides a redescription of the species and designation of a neotype specimen. The Caridina cucphuongensis Dang, 1980 is characterized by short rostrum with large teeth on the dorsal margin, long stylocerite, subrectangular endopod of male first pleopod, and short appendix interna of the male second pleopod.